2017
DOI: 10.7150/jca.21582
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of PET/CT in Target Delineation of MRI-negative Cervical Lymph Nodes In Intensity-Modulated Radiation Therapy Planning for Nasopharyngeal Carcinoma

Abstract: Introduction: In intensity-modulated radiation therapy (IMRT) planning for nasopharyngeal carcinoma (NPC), cervical lymph nodes (CLNs) that appear negative on magnetic resonance imaging (MRI) scans can be difficult to target. The purpose of this study was to assess the advantage of 18F-fluorodeoxyglucose positron emission tomography with computed tomography (18F-FDG PET/CT) for distinguishing MRI-negative CLNs and the effect of 18F-FDG PET/CT on diagnosis, target delineation, and dose prescription in IMRT plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(51 citation statements)
references
References 27 publications
(22 reference statements)
0
50
1
Order By: Relevance
“…Figure 1 shows the images of four representative patients. Primary tumor uptake was higher in 18 F-FDG (SUVmax 17.73 ± 6.84) than 68 Ga-FAPI (SUVmax 13.87 ± 5.13), but no signi cant differences were found (P =0.078, Table 2). We further compared the correlation between the uptake of two tracers and found that the SUVmax of 68 Ga-FAPI had no relationship with 18 F-FDG (r =0.227, p=0.416, Figure 2A).…”
Section: Primary Tumor Detection and Visual Evaluation Of Primary Tummentioning
confidence: 88%
See 4 more Smart Citations
“…Figure 1 shows the images of four representative patients. Primary tumor uptake was higher in 18 F-FDG (SUVmax 17.73 ± 6.84) than 68 Ga-FAPI (SUVmax 13.87 ± 5.13), but no signi cant differences were found (P =0.078, Table 2). We further compared the correlation between the uptake of two tracers and found that the SUVmax of 68 Ga-FAPI had no relationship with 18 F-FDG (r =0.227, p=0.416, Figure 2A).…”
Section: Primary Tumor Detection and Visual Evaluation Of Primary Tummentioning
confidence: 88%
“…Primary tumor uptake was higher in 18 F-FDG (SUVmax 17.73 ± 6.84) than 68 Ga-FAPI (SUVmax 13.87 ± 5.13), but no signi cant differences were found (P =0.078, Table 2). We further compared the correlation between the uptake of two tracers and found that the SUVmax of 68 Ga-FAPI had no relationship with 18 F-FDG (r =0.227, p=0.416, Figure 2A). The T staging of 68 Ga-FAPI was consistent with the MRI ndings in all the patients, but the T staging in one of the patients was underestimated by 18 F-FDG (Table 1).…”
Section: Primary Tumor Detection and Visual Evaluation Of Primary Tummentioning
confidence: 88%
See 3 more Smart Citations